Phosphate composition of uranium sooty (blacks) as indicator of their biogenic nature - O. A. Doynikova (Известия высших учебных заведений: Геология и разведка)
The biogenic aspect of tetravalent uranium mineral-formation in a hypergenesis’ zone is considered in the light of the up-to-date data of a geomicrobiology and environmental-mineralogy, studying products of bacterial biorecultivation. The analysis of literary and author’s data on phosphate U4+ ningyoite is led to the following conclusions: the source of phosphorus for ningyoite formation is organic material of the decomposed plant debris in sedimentaryrock strata; mineralization U4+ is caused by the activity of a bacterial microflora; the aerobic-anaerobic community of the microorganisms needs to be considered on an equal basis with especially geochemical characteristics of the environment as the most important component of uraniumsooty ore formation.